Nictemeral Variation of Physical Chemical and Biological Parameters of Ribeirão das Cruzes, Araraquara-SP - Santos, Vitor Rocha (2010)
Improper use of water, its degradation and irregular distribution can affect the quantity and quality needed for future generations, as well as create conflicts of interest between the industrial, urban and agricultural segments. In this context, it is of great importance the realization of studies on the quality of the hydric resources based on the analysis of temporal variation of limnological parameters. This study was conducted in the sub-basin of Ribeirão das Cruzes, which contributes to the water supply of the city of Araraquara (SP) around 30% of all water captured and offered to the population. The objective of this research was to compare the water quality of river upstream and downstream of effluent discharge from a local treatment station in a 24 hour period (diurnal cycle variation). Data collection, comprising the period of one day, was done in order to observe the dynamics of operation and range of variation of the ecological processes in the studied system. The parameters analyzed showed significant variations in the sections of the upstream and downstream from the effluent discharge. With the nictemeral analysis it is evident the influence of effluents on the the waters of Ribeirão das Cruzes, especially during certain periods of the day.